Association of electrographic left ventricular hypertrophy with incident hypertension among the Tokyo 1964 Olympic athletes: a 50-year follow-up study - Ashikaga, K.; Yoneyama, K.; Musha, H.; Akashi, Y. J.; Kawahara, T. (Sport Sciences for Health, 2022)
Background Hypertension is an important cardiovascular risk factor that affects cardiac remodeling. Left ventricular hypertrophy (LVH) is a type of cardiac remodeling and a significant risk factor for adverse outcomes. Elite athletes can develop LVH, also called athlete`s heart. While LVH is a reversible change, it is sometimes persistent. It is unclear whether athletes with LVH will suffer from future health disadvantages such as hypertension. Lifestyle-related factors may be involved in long-term health problems; nonetheless, the relationship between LVH and lifestyle is unclear.